Cell Interplay in Osteoarthritis - Li, Zihao; Huang, Ziyu; Bai, Lunhao (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA) is a common chronic disease and a significant health concern that needs to be urgently solved. OA affects the cartilage and entire joint tissues, including the subchondral bone, synovium, and infrapatellar fat pads. The physiological and pathological changes in these tissues affect the occurrence and development of OA. Understanding complex crosstalk among different joint tissues and their roles in OA initiation and progression is critical in elucidating the pathogenic mechanism of OA. In this review, we begin with an overview of the role of chondrocytes, synovial cells (synovial fibroblasts and macrophages), mast cells, osteoblasts, osteoclasts, various stem cells, and engineered cells (induced pluripotent stem cells) in OA pathogenesis. Then, we discuss the various mechanisms by which these cells communicate, including paracrine signaling, local microenvironment, co-culture, extracellular vesicles (exosomes), and cell tissue engineering. We particularly focus on the therapeutic potential and clinical applications of stem cell-derived extracellular vesicles, which serve as modulators of cell-to-cell communication, in the field of regenerative medicine, such as cartilage repair. Finally, the challenges and limitations related to exosome-based treatment for OA are discussed. This review paper provides a comprehensive summary of key cells that might be targets of future therapies for OA.